Dialectics Unbound: On the Possibility of Total Writing - Kennel, Maxwell (Book collections on Project MUSE., 2013)
"Dialectics Unbound: On the Possibility of Total Writing re-imagines figures of ontological totality, in and out of writing, first by exploring some lineages of the dialectic, and second by engaging thinkers such as Theodor Adorno and his assertion of nonidentity, Julia Kristeva and her positing of a fourth term of the dialectic, and Fredric Jameson's treatment of the dialectic as an open totality. By articulating a concept of totalization-without-totality, Dialectics Unbound seeks to free the concept of the dialectic from the violence of closure, and then to take this unbound dialectics to the work of writing through a brief examination of parataxis and aphoristics as approaches to writing, both possible and impossible"--https://punctumbooks.com/titles/dialectics-unbound/ accessed 05/31/2020.